2019
DOI: 10.21608/assjm.2019.44932
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Soya bean (glycine max l.) Plants Growth, Yield and Seed Quality by using Putrescine, Benzyladenine and Yeast Extract

Abstract: Two field experiments in randomized complete Block design (RCBD) were conducted at the experimental farm, Faculty of Agriculture Moshtohor, Benha university, Egypt during 2016 and 2017 seasons to study the effect of Putrescine at 5 and 10 mg/L, Benzyl adenine (BA) at 20 and 40 mg/L and yeast extract at 50 and 100 ml/L on growth, photosynthetic pigments, phytohormones content, anatomical structures, flowering, characteristics; seed fuelling and yield of Soybeans (Glycine max L.) plants. Results showed that diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 7 publications
2
5
0
Order By: Relevance
“…As well as the same results are recorded by several investigators in different plant species Abd El-Dayem (1999) on fodder beet plants, Abd El-Dayem et al, (2012) on sesame plants; Ismail (2016) on wheat plants and Zewail et al, (2019) they showed that foliar application of BA increased yield and its components of soybean plants. This increments in root yield characteristics of sugar beet plants may be due to a reflection of BA and yeast extract beneficial effects on vegetative growth, total leaves are (Table, 1) photosynthetic pigments content, the amount of metabolites (total carbohydrates and crude protein in leaves), absorption and translocation mineral contents (N, P and K) ( Table, 3), as well enhancing sink activity and endogenous growth hormone levels Bondok (1996); El-Desuoky et al, (2011) and Zewail et al, (2019) which in turn could lead to an increase in the rate of net amount of photosynthetic assimilate production and transport from sites of synthesis in leaf tissue source to sites of accumulation in storage organs (sink) of roots Patrick (1982) and consequently increase root yield of sugar beet plants. In this regard, Bondok (1996) concluded that kinetin treatments nearly lead to an increase of cytokinin levels in both shoots and roots which increase chlorophyll content also lead to accelerate cambial activity and cell division which reflected itself on root and sugar yield of sugar beet plants.…”
Section: Root Yield Characteristics and Root Quality At Harvest Time:supporting
confidence: 81%
See 4 more Smart Citations
“…As well as the same results are recorded by several investigators in different plant species Abd El-Dayem (1999) on fodder beet plants, Abd El-Dayem et al, (2012) on sesame plants; Ismail (2016) on wheat plants and Zewail et al, (2019) they showed that foliar application of BA increased yield and its components of soybean plants. This increments in root yield characteristics of sugar beet plants may be due to a reflection of BA and yeast extract beneficial effects on vegetative growth, total leaves are (Table, 1) photosynthetic pigments content, the amount of metabolites (total carbohydrates and crude protein in leaves), absorption and translocation mineral contents (N, P and K) ( Table, 3), as well enhancing sink activity and endogenous growth hormone levels Bondok (1996); El-Desuoky et al, (2011) and Zewail et al, (2019) which in turn could lead to an increase in the rate of net amount of photosynthetic assimilate production and transport from sites of synthesis in leaf tissue source to sites of accumulation in storage organs (sink) of roots Patrick (1982) and consequently increase root yield of sugar beet plants. In this regard, Bondok (1996) concluded that kinetin treatments nearly lead to an increase of cytokinin levels in both shoots and roots which increase chlorophyll content also lead to accelerate cambial activity and cell division which reflected itself on root and sugar yield of sugar beet plants.…”
Section: Root Yield Characteristics and Root Quality At Harvest Time:supporting
confidence: 81%
“…Also, similar results were reported by Ramadan, Amany et al, (2005); Ibrahim et al, (2010); Ismail (2016); El-Emary et al, (2018). and Zewail et al, (2019) They found that foliar application with BA and yeast extract increased fresh and dry weights of shoots, endogenous phytohormons levels and photosynthetic pigments content in leaves of soybean plants. Also, the above mentiond results of yeast extract are in harmony with those obtained by Mahmoud, Asmaa (2004); El-Tarabily (2004); Mekki and Ahamed (2005); Wanas (2007); El-Desouky et al, (2011) and Zewial et al .,(2019).…”
Section: Fresh and Dry Weights Of Root And Leaves (G/plant)mentioning
confidence: 96%
See 3 more Smart Citations